Anticarcinogenic and antitumorigenic effect of Garlic and factors affecting its activity: A Review - Omar, Syed Haris; U.H., Abshar; M., Nehal (Pharmacognosy Reviews)
Garlic (Allium satium) belongs to family Liliaceae, contains various chemical compounds which are helpful in prevention and treatment of different types of cancer. Both oil and water-soluble allyl sulfur compounds from garlic have been found to possess antitumorigenic properties. Generally, oil-soluble allyl sulfur compounds are more effective antiproliferative agents than their water-soluble counterparts. The ability of these compounds to suppress proliferation is associated with a depression in cell cycle progression and the induction of apoptosis. This depression in cell division coincides with an increase in the percentage of cells blocked in the G2/M phase of the cell cycle. A depression in p34cdc2 kinase may account for this blockage in cell division. Preclinical and clinical studies suggested that allicin- a compound responsible for the antitumour and antitumorigenic effect. Part of the protection from these compounds probably inhibit the enzyme cytochrome P450 2E1. This enzyme activates a number of xenobiotic substances, including carcinogens such as nitrosamines, hydrazines and halogenated hydrocarbons. This review will focus on evidence that garlic is anticarcinogenic and antitumorigenic and identify some dietary components that should be considered as important variables when assessing the true anticancer potential of garlic and the factor affecting its activity.
Keywords: Garlic; antitumour; antitumorigenic; allyl sulfur